Biomedical characterization techniques and analysis - Tjin, Swee Chuan. (2012)
Nanoscale modelling of biological systems is an emerging topic in nanotechnology andnanoengineering. Visual and force feedback simulation could be a very important andsometimes the only tool used in nanoengineering for virtual and even real experiments atnanoscale level. The computer simulation of assembling molecules has been studiedintensively in the field of computer‐aided rational drug design. The assembly of molecules ina three‐dimensional space or molecular docking is used for rational drug design where aligand docks onto a receptor. The computer‐aided design systems allow real‐time interactive visualization and manipulation of molecules in virtual environment. These techniques helpthe user to understand molecular interactions, and to evaluate the design of pharmaceuticaldrugs.